Multicenter database registry for endoscopic retrograde cholangiopancreatography: Japan Endoscopic Database Project. Issue 4 (3rd October 2019) - Kato, Masayuki; Tanaka, Kiyohito; Kida, Mitsuhiro; Ryozawa, Shomei; Matsuda, Koji; Fujishiro, Mitsuhiro; Saito, Yutaka; Ohtsuka, Kazuo; Oda, Ichiro; Katada, Chikatoshi; Kobayashi, Kiyonori; Hoteya, Shu; et al.
Abstract : Background and Aim: Few studies have reported on a national, population‐based endoscopic retrograde cholangiopancreatography (ERCP) database. Hence, in 2015, we established a multicenter ERCP database registry, the Japan Endoscopic Database (JED) Project in preparation for a nationwide endoscopic database. The objective the present study was to evaluate this registry before the establishment of a nationwide endoscopic database. Methods: From 1 January 2015 to 31 March 2017, we collected and analyzed the ERCP data of all patients who underwent ERCP in four participating centers in the JED Project based on the JED protocol. Results: Four centers carried out 4104 ERCP on 2173 patients. Data entry of ERCP information (age, 100%; gender, 100%; American Society of Anesthesiologists Physical Status Classification System, 74.5%; scope, 92.7%; time to ERCP, 100%; antithrombotic drug information, 55.0%; primary selective common bile duct [CBD] cannulation methods, 73.0%; number of attempts at primary selective CBD cannulation, 67.6%; overall selective CBD cannulation methods, 68.9%; ERCP procedure time, 66.3%; fluoroscopy time, 65.1%; adverse events, 74.9%; serum amylase levels 1 day post‐ERCP, 36.5%) was accurately extracted from the four centers. Success rate of CBD cannulation by level of ERCP difficulty was 98.5%, 99.0%, and 96.4% in grades 1, 2, and 3, respectively. Complication rate by overall selective CBD cannulation method was 5.6%, 7.6%, and 10.5% in the contrast‐assisted technique, guidewire‐assisted technique, and cross‐over method, respectively. Conclusion: Data from this evaluation of the JED Project, a multicenter ERCP database registry, suggest the feasibility of establishing a nationwide ERCP database and its challenges.